Aerobic and anaerobic energy conversion during high-intensity exercise - Ward-Smith, A. J. (Medicine & Science in Sports & Exercise, 1999)
Purpose: The aim of the study is to compare data on anaerobic and aerobic energy conversion during exercise of high intensity leading to exhaustion. Several different data sources are used, including data extracted from mathematical analyses of world and Olympic running records, data from laboratory tests, and data based on biochemical information.